2012
DOI: 10.1097/sih.0b013e3182578eae
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Video-Assisted Debriefing Versus Oral Debriefing Alone at Improving Neonatal Resuscitation Performance

Abstract: Using this study design, we failed to show a significant educational benefit of video-assisted debriefing. Although our results suggest that the use of video-assisted debriefing may not offer significant advantage over oral debriefing alone, exactly why this is the case remains obscure. Further research is needed to define the optimal role of video review during simulation debriefing in neonatal resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 29 publications
2
57
0
4
Order By: Relevance
“…5 Therefore, the use of adjuncts during debriefing, such as video playback and quantitative performance data, has promise in improving outcomes in simulated and clinical contexts. 25,33,[40][41][42] Clinicians in ED, neonatology, and trauma care have implemented real-time video capture of resuscitation events in the clinical environment as part of local quality programs. [43][44][45][46][47][48][49][50][51] Nadler et al 25 demonstrated that including video recordings of neonatal resuscitations in debriefings improved teamwork in future neonatal resuscitations.…”
Section: Debriefing In the Emergency Department After Clinical Eventsmentioning
confidence: 99%
“…5 Therefore, the use of adjuncts during debriefing, such as video playback and quantitative performance data, has promise in improving outcomes in simulated and clinical contexts. 25,33,[40][41][42] Clinicians in ED, neonatology, and trauma care have implemented real-time video capture of resuscitation events in the clinical environment as part of local quality programs. [43][44][45][46][47][48][49][50][51] Nadler et al 25 demonstrated that including video recordings of neonatal resuscitations in debriefings improved teamwork in future neonatal resuscitations.…”
Section: Debriefing In the Emergency Department After Clinical Eventsmentioning
confidence: 99%
“…42 Video-assisted debriefing: 1 randomized study compared the effectiveness of video-assisted debriefing to oral debriefing alone in the context of simulated neonatal resuscitation and found small or negligible effects favoring video-assisted debriefing for time skills (N = 30, ES = 0.12) and nontime skills (ES = 0.27). 43 …”
Section: Figurementioning
confidence: 99%
“…[26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
“…Results in the literature are mixed concerning the effectiveness and appreciation of peer oral feedback compared with expert oral feedback (Burgess & Mellis, 2015;English et al, 2006;Krause et al, 2017;Yeh et al, 2015). In addition to the debriefing process, reviewing one's performance using a video may be a useful instructional supplement, but the literature regarding the effectiveness of video-enhanced learning is inconclusive (Birnbach et al, 2002;Farquharson et al, 2013;Oseni et al, 2017;Ruesseler et al, 2017;Savoldelli et al, 2006;Sawyer et al, 2012). Ten Cate et al stated that peer-assisted learning offers educational value to students on their own cognitive level, and it creates a comfortable and safe educational environment to enhance the efficiency of the learning process (Ten Cate & Durning, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that video feedback is a potent and efficacious teaching instrument (Birnbach et al, 2002;Farquharson, Cresswell, Beard, & Chan, 2013;Oseni et al, 2017;Ruesseler, Sterz, Bender, Hoefer, & Walcher, 2017), while others found no significant effect (Byrne et al, 2002 Sawyer et al, 2012) or, in some cases, a worse outcome in comparison to oral feedback alone (Savoldelli et al, 2006). However, video feedback combined with peer or expert feedback improved students' communication skills (Krause, Schmalz, Haak, & Rockenbauch, 2017).…”
Section: Introductionmentioning
confidence: 99%